Experimental investigations on morphology controlled bifunctional NiO nano-electrocatalysts for oxygen and hydrogen evolution. (29th November 2022) - Manjunath, Vishesh; Bimli, Santosh; Biswas, Rathindranath; Didwal, Pravin N.; Haldar, Krishna K.; Mahajan, Mangesh; Deshpande, Nishad G.; Bhobe, Preeti A.; Devan, Rupesh S.
Abstract: Developing a single electrocatalyst effective for both oxygen and hydrogen evolution remains challenging. Although an attempt to utilize a single electrocatalyst for overall water splitting is made, there still exist several issues of efficiency and stability of the electrocatalyst. Hence, the present study reports on morphology-controlled NiO electrocatalyst, a single electrocatalyst for oxygen and hydrogen evolution. The cubic phase NiO nanoparticles and nanoplates of diameter and thickness <10 nm delivered surface-to-volume ratios of 0.078 and 0.083, respectively. XRD and TEM confirm the formation of NiO nanostructures, where morphology transformed independently of the chemical composition. XPS and EXAFS confirm the 2+ oxidation state of Ni ions and its octahedral coordination with oxygen. The 0D nanoparticles providing a larger surface area and active sites offered the overpotentials of 373 and 268 mV for OER and HER activity, respectively, and performed well than the 2D porous NiO nanoplates. The chronoamperometry and repetitive LSV cyclic studies confirmed the excellent long-term stability of 0D NiO nanoparticles in basic and acidic mediums during electrocatalytic water splitting reactions, owing to its increased electrochemically exposed active sites. Graphical abstract: Morphology-controlled bi-functional 0D NiO nanoparticles (left upper panel) of cubic crystalline (lower left panel) phase delivered excellent electrocatalytic hydrogen (upper right panel) and oxygen (lower right panel) evaluation. Image 1 Highlights: Bifunctional NiO nano-electrocatalyst for water splitting. Morphology transformation from 0D to 2D nanostructures using co-precipitation method. Ni 2+ /Ni 3+ transition-assisted water splitting in 0D NiO nanoparticles. Larger surface active sites provide overpotential 373 and 268 mV for OER and HER.